Penggunaan Media Papan Pintar Untuk Meningkatkan Hasil Belajar Matematika Kelas I di SDN Ngijo 1 - Siti Noor Laili Mahfukhatus Sofa; Nursiwi Nugraheni; Artiningsih Artiningsih (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This study aims to improve the learning outcomes of class I students at SDN Ngijo 01 Semarang in the material form of shapes using smart board media. This type of research is Classroom Action Research. This research consists of 5 cycles. Each of these cycles includes the stages of planning, implementing, observing and reflecting. The research subjects were class I SDN Ngijo 01 Semarang, totaling 28 students consisting of 10 male students and 18 female students. Data collection methods in this study are tests and observations. The research instruments used in this study were test questions and observation sheets. The data analysis technique used in this study is a qualitative descriptive technique with percentages. The success criteria achieved by students and teachers in this study were seen from changes towards improvement and increasing student learning outcomes. The results of the study show that the use of smart board media is able to improve student learning outcomes in the shape material. This can be seen from the percentage of students' pre-action scores that achieved 39.3% classical mastery level, namely 11 out of 28 participants. In cycle I 64% completeness classical, cycle II 68% completeness classical, cycle III 71% completeness classical, cycle IV 75% completeness classical, cycle V 89% completeness classical. Due to the increase in student learning outcomes from having met the target of 85% so that the cycle ends in cycle V. Students show activeness in the learning process and students also understand more because they have direct learning experiences using smart board media.